Post-partum paraplegia following spinal anaesthesia: a report of two rare cases. Issue 3 (9th March 2023) - Hussain, Tosaddeque; Ghosh, Indranil; Gerber, Christopher; Basu, Anindya; Tiwari, Mona
Abstract: Pregnancy and lumbar puncture are rare instances that can precipitate sudden onset paraplegia in patients with otherwise slow-growing intradural tumours. Surgeons and anaesthesiologists should be aware of the etiological factors leading to pregnancy- and delivery-related rapid tumour growth and its complications. Lumbar puncture-related complications leading to acute precipitation of neurological symptoms must be addressed promptly for favourable outcome in such patients. We describe the report of two patients who developed acute onset paraparesis after spinal anaesthesia for caesarean section. Both were found to be having undiagnosed spinal tumours and managed surgically. We recommend urgent MRI in cases of acute onset non-resolving paraparesis in the peripartum period, for timely diagnosis and management of this rare clinical entity.